UNCOVERING TEACHER AWARENESS AND UNDERSTANDING OF DYSLEXIA: INSIGHTS FROM A SURVEY-BASED STUDY ON THE LEARNING LANDSCAPE OF DYSLEXIC STUDENTS (CAHIERS MAGELLANES-NS, 2024)
Educators play a pivotal role in shaping young minds, yet many remain unaware of dyslexia, a specific neurobiological learning disability characterized by difficulties with word recognition, poor spelling, and letter-sound decoding. These challenges arise from atypical wiring in the Occipito Temporal region of the brain. The lack of awareness among educators leads to missed early identification of dyslexic students. This pilot study, involving visits to dyslexic schools in Chennai and a survey of 100 educators from Chennai, Trichy, and Coimbatore in Tamil Nadu, revealed a significant gap in educators' understanding and knowledge of dyslexia. The findings underscore the critical need for intensive dyslexia training for educators to ensure early identification and appropriate support for dyslexic students. Enhancing educators' awareness and understanding of dyslexia is essential for providing effective support and enabling dyslexic learners to reach their full potential. This article highlights the urgency of increasing dyslexia awareness and education among educators to bridge the knowledge gap and better support dyslexic students